SISTEM-PENDUKUNG KEPUTUSAN PENERIMA-BEASISWA DENGAN METODE WEIGHTED-PRODUCT PADA MTS. MIFTAHUL ULUM JARAKKULON-JOGOROTO JOMBANG - Marpuad; Setyo Permadi , Ginanjar; Fatkhur Rizal , Muhammad (Inovate, 2024)
Decision support system (DSS) is a computer-based system that helps during the decision-making process. Decision support systems are computer-based information systems through adaptability, interaction and flexibility, and are specifically developed to support unstructured management problem solving to improve decision quality. This decision support system can assist schools in the decision-making process to determine scholarship recipients at Mts Miftahul Ulum Jarakkulon-Jogoroto Jombang. In this decision support system, criteria are needed to be able to determine who will be selected as receiving the scholarship. In developing this decision support system, the authors use the methodweighted product as a method for decision making. Methodweighted product chosen because it is a weighted sum to find the weighted sum of the performance ratings for each alternative across all attributes. So the decision to receive a scholarship with the highest score in this system is the 27th choice with a value of 0.043 Keywords : Decision Support System, Selection of Scholarship Recipients, Weighted-Product.